2013
DOI: 10.1007/s00264-013-2112-1
|View full text |Cite
|
Sign up to set email alerts
|

Neglected patellar tendon ruptures—a simple modified reconstruction using hamstrings tendon graft

Abstract: Purpose We hereby describe a cost effective and simple anatomical reconstruction without requirement for allograft or implants for neglected chronic patellar tendon injuries. This has been validated in seven patients with an average follow up of greater than three years resulting in good outcome. Methods Seven patients (six males, one female) of mean age 41.8 years (range up to 57 years) presented with neglected patellar tendon injury. The time since injury ranged between three months and three years (average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 19 publications
(24 reference statements)
1
51
0
2
Order By: Relevance
“…La reconstrucción del tendón patelar con el uso de autoinjertos ipsilaterales de STG es segura, efectiva y validada desde el punto de vista clínico y funcional. 9, [25][26][27] Además, es un constructo de resistencia probada 34,35 (la configuración en doble banda aporta una resistencia máxima a la carga de 2330N), que asegura una integración adecuada de los injertos. 28 Estos últimos, al ser cosechados rutinariamente en la reconstrucción del ligamento cruzado anterior, permiten realizar una cirugía técnicamente reproducible, pese a la infrecuencia de esta patología.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La reconstrucción del tendón patelar con el uso de autoinjertos ipsilaterales de STG es segura, efectiva y validada desde el punto de vista clínico y funcional. 9, [25][26][27] Además, es un constructo de resistencia probada 34,35 (la configuración en doble banda aporta una resistencia máxima a la carga de 2330N), que asegura una integración adecuada de los injertos. 28 Estos últimos, al ser cosechados rutinariamente en la reconstrucción del ligamento cruzado anterior, permiten realizar una cirugía técnicamente reproducible, pese a la infrecuencia de esta patología.…”
Section: Discussionunclassified
“…Se estima que el diámetro combinado de esos injertos (duplicados) varía en rangos que fluctúan desde los 4 a los 6,5mm. 26 En revisiones, se instalan 2 anclas de titanio en el polo inferior de la rótula y se resutura el tendón lesionado con la técnica de Krackow, 31 para asegurar una adecuada dispersión de las fuerzas a lo largo de la sutura. Las anclas deberían fijarse a aproximadamente 2mm de la superficie articular.…”
Section: Técnica Quirúrgicaunclassified
“…Multiple operation techniques with different substances for augmentation have been described for extensor mechanism repair. Autograft and allograft tendons, absorbable and non-absorbable sutures, and wires have been used with good results (8,(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Elsayed Massoud treated twelve fresh patellar tendon ruptures by direct repair and augmentation with absorbable suturing between the patella and tibial tuberosity with good functional outcomes (23). Sundararajan et al reported excellent outcomes of seven cases of chronic patellar tendon rupture reconstructed with semitendinosus and gracilis tendon autografts (24). Milankov and colleagues used a double-wire loop to reinforce a chronic patellar tendon rupture reconstruction with contralateral bone-patellar tendon-bone autograft (27).…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, the repair techniques have progressed from simple suture with catgut or silk to wire-reinforced repair, pull-out suture fixation through patella, suture anchor fixation, tendon lengthening repair, Scuderi technique, allograft, autograft, and synthetic materials [ 1 , 4 , 6 12 ]. However, no literature has reported the result using arthroscopy.…”
Section: Introductionmentioning
confidence: 99%